Research of low noise pHEMT transistors in equipment for microwave radiometry using numerical simulation. (December 2020) - Tikhomirov, V G; Gudkov, A G; Agasieva, S V; Yankevich, V B; Popov, M K; Chizhikov, S V
Abstract: The numerical impact modeling of some external effects on devices based on AlGAs/InGaAs/GaAs heterostructures (pHEMT) was carried out. The mathematical model was created that allowed to predict the behavior of the drain current depending on condition changes on the heterostructure in the barrier region and to start the process of directed construction optimization of the devices based on AlGaAs/InGaAs/GaAs pHEMT with the aim of improving their noise characteristic.